Geography and archaeology in the Sondondo valley, Ayacucho - Pérez Calderón, Ismael (2021)
The main purpose of this work is to present the characteristics of the landscape valley, Lucanas province, Ayacucho department; using GPS we were able to directly locate, recognize and record different kinds of archaeological remains, grouped in rock art (wells and models), funerary structures (tombs and pukullos) and rooms, terraces, canals, acueducts (roads and lagoons (qochas), attributed to different times of the pre-hispanic world, with emphasis onnthe Wari period and, distributed in an articulated manner in various life zones and altitudinal floors of the middle valley of the sondondo river, a tributary of the Pampas river on the Atlantic Ocean slone.